ANALISIS PENERAPAN SEMA NOMOR 2 TAHUN 2023 TERHADAP PENETAPAN NOMOR 423/PDT.P/2023/PN Jkt.Utr TENTANG PERKAWINAN BEDA AGAMA - NIM. A1011201216, LUKMANUL HAKIM (Jurnal Fatwa Hukum, 2025)
Abstract The issue of interfaith marriage in Indonesia has long caused legal uncertainty, leading to diverse interpretations and practices in the courts. To address this and establish uniformity in legal implementation, the Supreme Court (MA) issued the Supreme Court Circular Letter (SEMA) Number 2 of 2023, which firmly reaffirms the prohibition of interfaith marriage registration by district courts. However, shortly after the SEMA was issued, the North Jakarta District Court (PN Jkt.Utr) rendered Decision Number 423/Pdt.P/2023/PN Jkt.Utr, which, on the contrary, granted the application for interfaith marriage registration. This normative juridical legal research aims to analyze the judge's legal considerations in granting the application and to determine the legal consequences, particularly in the context of SEMA Number 2 of 2023. Employing the statutory and case approaches, this study examines the conflict between the legal principles underlying the decision. The research findings indicate that the judge's considerations are dominated by a progressive legal approach. The judge prioritized the principles of substantive justice and social utility to protect the human rights of the applicants, prevent discrimination, and provide legal and administrative certainty (such as status of children and inheritance rights) for the interfaith couple. However, this approach implies setting aside the formal legal certainty reinforced by SEMA Number 2 of 2023. The legal consequence is that the marriage is practically recorded and administratively valid, yet normatively, this stipulation potentially undermines the authority of the SEMA, creates a lack of uniformity in judicial practice (forum shopping), and leads to broader legal uncertainty within the national judicial system. Keywords: Interfaith Marriage, Judge's Legal Consideration, SEMA Number 2 of 2023 Abstrak Isu mengenai perkawinan beda agama di Indonesia telah lama menimbulkan ketidakpastian hukum, memicu keragaman penafsiran dan praktik di pengadilan. Untuk mengatasi hal ini dan menciptakan kesatuan penerapan hukum, Mahkamah Agung (MA) menerbitkan Surat Edaran Mahkamah Agung (SEMA) Nomor 2 Tahun 2023 yang secara tegas menegaskan larangan pencatatan perkawinan beda agama oleh pengadilan negeri. Namun, tidak lama setelah SEMA tersebut terbit, Pengadilan Negeri Jakarta Utara (PN Jkt.Utr) mengeluarkan Putusan Nomor 423/Pdt.P/2023/PN Jkt.Utr yang justru mengabulkan permohonan pencatatan perkawinan beda agama. Penelitian hukum yuridis normatif ini bertujuan untuk menganalisis pertimbangan hukum hakim dalam mengabulkan permohonan tersebut dan mengetahui akibat hukumnya, khususnya dalam konteks SEMA Nomor 2 Tahun 2023. Dengan menggunakan pendekatan perundang-undangan dan kasus, penelitian ini meneliti konflik antara asas hukum yang mendasari putusan tersebut. Hasil penelitian menunjukkan bahwa pertimbangan hakim didominasi oleh pendekatan hukum progresif. Hakim mengutamakan asas keadilan substantif dan asas kemanfaatan sosial untuk melindungi hak asasi manusia para pemohon, menghindari diskriminasi, serta memberikan kepastian hukum dan administrasi (seperti status anak dan hak waris) bagi pasangan beda agama. Namun, pendekatan ini berimplikasi pada dikesampingkannya asas kepastian hukum formal yang diperkuat oleh SEMA Nomor 2 Tahun 2023. Akibat hukumnya, secara praktis perkawinan menjadi tercatat sah secara administratif , tetapi secara normatif penetapan ini berpotensi melemahkan wibawa SEMA, menciptakan ketidakseragaman praktik pengadilan (forum shopping), dan memunculkan ketidakpastian hukum yang lebih luas dalam sistem peradilan nasional. Kata Kunci: Perkawinan Beda Agama, Pertimbangan Hukum Hakim, SEMA Nomor 2 Tahun 2023.